Kualitas ikan cakalang (Katsuwonus pelamis) hasil penangkapan one day fishing di Teluk Bone, Indonesia: Kualitas ikan cakalang (Katsuwonus pelamis) hasil penangkapan one-day fishing di Teluk Bone, Indonesia - Maskur, Muhammad; Alauddin, Muhammad Hery Riyadi; Saridewi, Tri Ratna; Siregar, Resmi Rumenta; Kusmedi, Bombongan; Najih, Mohammad Roin; Harahap, Kurnia Sada (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
One-day fishing, a brief fishing endeavor lasting less than 24 h, entails bringing the catch directly to shore, thereby preserving the freshness of the captured fish. Nonetheless, studies investigating the correlation between one-day fishing techniques and catch quality are scarce. This study aimed to determine the quality of skipjack tuna (Katsuwonus pelamis) caught in one-day fishing in Gulf of Bone, South Sulawesi, Indonesia. The research methods included organoleptic, physicochemical (temperature and pH), microbiological (total plate count/TPC), and histamine level analyses. The sampling method used purposive sampling by means of skipjack tuna caught from three one-day fishing fleets, each taking 1–2 fish with a weight of between 1.8-2 kg, and then analyzed in a quality testing laboratory within three hours after landing. The organoleptic test results showed very good quality, with values ranging from 8.23 to 8.81. The physicochemical parameters showed a fish meat temperature of 3.42–5°C and pH of 6.21–6.51, which are still within the range of fresh fish. The TPC value was 9.1×10³–9.9×10³ CFU/g, which is far below the threshold of national and international standards. Histamine levels ranged from 3.46–4.22 mg/kg, well below the maximum limit of 30–50 mg/kg set by the food safety standards. Overall, the study results confirmed that the one-day fishing method using trolling lines can produce skipjack tuna with excellent organoleptic, physicochemical, and microbiological qualities that are safe for human consumption.